Pietra ollare Artefact from Červar Porat (Istria, Croatia) - Tibljaš, Darko (Array, 2006)
During excavations of Roman villa rustica Červar-Porat, which were run under supervision of Vesna Jurkić-Girardi in 1976, peculiar vessel fragment was discovered. It has grey-green colour, and shows traces of manufacturing by means of lathe. The fragment was investigated by X-ray powder diffraction method. Analysis revealed that the only constituent is the chlorite group mineral. Mineral composition together with visible schistosity indicates that source material was chlorite-schist, a low-grade metamorphic rock. Such material is one of different lithologies being enclosed by the term pietra ollare. Vessels made by analogous processes from similar materials have already been found at several localities at Croatian Adriatic coast. Adequate raw materials can not be found in Istria and its nearest surroundings therefore import of this kind of vessels should be presumed. Most probably the material originates from Alpine realm.